Josephus's The Jewish War: a biography - Goodman, Martin (Lives of great religious books, 2019)
Cover -- Title -- Copyright -- CONTENTS -- LIST OF ILLUSTRATIONS -- PREFACE -- CHAPTER 1 Beginnings -- Josephus the Man -- The Book -- CHAPTER 2 Early Years (100-1450) -- The Book among Early Christians (100-600) -- The Book among Jews (100-1450) -- Fame in the Christian World (600-1450) -- CHAPTER 3 Rediscovery of the Greek Book (1450-1750) -- Christians 1450-1750 -- Jews 1450-1750 -- CHAPTER 4 Controversy -- Doubts about Josephus -- The Book among Christians -- The Book among Jews -- EPILOGUE The Present and Future of the Jewish War -- APPENDIX Passages with a Life of Their Own -- NOTES -- FURTHER READING -- INDEX.